Rhinonyssus nenecoi sp. nov. (Mesostigmata: Rhinonyssidae); a new nasal mite from Daption capense (Procellariiformes: Procellariidae) - Gastal, Silvia Bainy; Mascarenhas, Carolina Silveira; Bugoni, Leandro (Zenodo, 2023)
Gastal, Silvia Bainy, Mascarenhas, Carolina Silveira, Bugoni, Leandro (2023): Rhinonyssus nenecoi sp. nov. (Mesostigmata: Rhinonyssidae); a new nasal mite from Daption capense (Procellariiformes: Procellariidae). Zootaxa 5301 (2): 269-276, DOI:10.11646/zootaxa.5301.2.7, URL: http://dx.doi.org/10.11646/zootaxa.5301.2.7